Transmit Waveform Optimization for Spatial-Frequency Diversity MIMO Radar in the Presence of Clutter - Yonghao Tang; Xiaofeng Ma; Weixing Sheng; Yubing Han (International Journal of Antennas and Propagation)
Benefitting from the independent target echoes of diversity channels, diversity MIMO radar can efficiently improve system performance, such as target detection and parameter estimation. Due to the fact that the RCS (radar cross section) of complex target may vary with the different transmitted carrier frequencies and array geometries, many recent researches study at the background of diversity MIMO radar equipped with widely separated array antennas or working at multiple carrier frequencies, respectively. In this paper, a new MIMO radar system combining the spatial and frequency diversities is investigated in the presence of signal-dependent clutter, which is called spatial-frequency diversity MIMO radar. With the prior information of target and clutter, a new method for joint optimization of transmitted waveforms and receiving filters is proposed to enhance the target detection ability of spatial-frequency diversity MIMO radar. Inspired by the MIMO communication system, the water-filling algorithm is introduced into the transmitted energy allocation problem for each carrier frequency channel. Simulation results show that the proposed system has a better performance in output signal-to-clutter-noise ratio (SCNR) compared to conventional diversity MIMO radar system.